Aging Alters the Aortic Proteome in Health and Thoracic Aortic Aneurysm. Issue 8 (5th May 2022) - Tyrrell, Daniel J.; Chen, Judy; Li, Benjamin Y.; Wood, Sherri C.; Rosebury-Smith, Wendy; Remmer, Henriette A.; Jiang, Longtan; Zhang, Min; Salmon, Morgan; Ailawadi, Gorav; Yang, Bo; Goldstein, Daniel R.
Abstract : Background: Aging enhances most chronic diseases but its impact on human aortic tissue in health and in thoracic aortic aneurysms (TAA) remains unclear. Methods: We employed a human aortic biorepository of healthy specimens (n=17) and those that underwent surgical repair for TAA (n=20). First, we performed proteomics comparing aortas of healthy donors to aneurysmal specimens, in young (ie, <60 years of age) and old (ie, ≥60 years of age) subjects. Second, we measured proteins, via immunoblotting, involved in mitophagy (ie, Parkin) and also mitochondrial-induced inflammatory pathways, specifically TLR (toll-like receptor) 9, STING (stimulator of interferon genes), and IFN (interferon)-β. Results: Proteomics revealed that aging transformed the aorta both quantitatively and qualitatively from health to TAA. Whereas young aortas exhibited an enrichment of immunologic processes, older aortas exhibited an enrichment of metabolic processes. Immunoblotting revealed that the expression of Parkin directly correlated to subject age in health but inversely to subject age in TAA. In TAA, but not in health, phosphorylation of STING and the expression of IFN-β was impacted by aging regardless of whether subjects had bicuspid or tricuspid valves. In subjects with bicuspid valves and TAAs, TLR9 expression positively correlated with subject age. Interestingly, whereas phosphorylation of STING was inversely correlated with subject age, IFN-β positively correlated with subject age. Conclusions: Aging transforms the human aortic proteome from health to TAA, leading to a differential regulation of biological processes. Our results suggest that the development of therapies to mitigate vascular diseases including TAA may need to be modified depending on subject age.